Virulence spectrum of pearl millet infecting populations of Magnaporthe grisea from Karnataka state in India - Prasad, Y P; Naik, M K; Nimmala, Naresh; Sharma, Rajan (Indian Journal of Plant Protection, 2024)
Pearl millet blast caused by ascomycete fungus Magnaporthe grisea (Herbert) (anamorph: Pyricularia grisea (Cook) Sacc.) has become a disease of economic importance in pearl millet cultivation in India. The use of resistant cultivars is the best approach to combat yield losses by M. grisea. However, the pathogen overcomes the resistance in a few years of releasing a resistant variety, making resistance breeding a constant challenge. To mitigate this, regular monitoring of virulence pattern adapted by the pathogen is essential. Seventy-four blast infected leaf samples were collected from the major pearl millet growing regions of north Karnataka, and single-cell pure cultures were established for 36 M. grisea isolates. Under greenhouse conditions, all the thirty-six isolates were subjected to virulence diversity analysis using a set of host differentials. Based on disease reaction (virulent = score ≥ 4 and avirulent = score ≤ 3 on a 0-to- 9 scale) on host differentials, the tested isolates were clustered into four pathogenic groups/pathotypes (group 1, 2, 3, and 4). Maximum 23 isolates belonged to group 3 with a compatible reaction on all the ten host differentials, followed by the second-largest pathogenic group/pathotype-1 that comprised nine isolates virulent on all the genotypes except IP 21187-P1. Isolates falling in group 2 (3 isolates) were avirulent on ICMR 1103 and IP 21187-P1 and virulent on the rest of the genotypes. Group 4 contained only one isolate, having avirulent reaction on ICMR 06444 and IP 21187-P1. The group 2 was found to be a new pathotype in addition to 14 pathotypes reported earlier from pearl millet infecting populations of M grisea. The high virulence levels found in M. grisea isolates necessitates constant tracking of M. grisea populations to predict blast resistance breakdown in Indian pearl millet cultivars.